Aristotle De animalibus. Michael Scot's Arabic-Latin translation, volume 1a: Books I-III: History of animals : a critical edition with an introduction, notes and indices - Aristotle, (Aristoteles Semitico-Latinus;, 2019)
"Aristotle's De Animalibus was an important source of zoological knowledge for the ancient Greeks and for medieval Arabs and Europeans. In the thirteenth century, the work was twice translated into Latin. One translation was produced directly from the Greek by William of Moerbeke. An earlier translation, made available as a critical edition in the present volume for the first time, was produced through an intermediary Arabic translation (Kitāb al-Ḥayawān) by Michael Scot (1175--c. 1232). Scot's translation was one of the main sources of knowledge on animals in Europe and widely used until well into the fifteenth century. As a faithful translation of a translation produced by a Syriac-speaking Christian, the text contributes to our knowledge of Middle Arabic. The De Animalibus is composed of three sections: History of Animals (ten books), Parts of Animals (four books) and Generation of Animals (five books). Parts of Animals and Generation of Animals were published by Brill as Volumes 5.2 and 5.3 of the book series ASL in 1998 (ASL 5.2) and 1992 (ASL 5.3). The present Volume 5.1.a contains the first section of Scot's translation of History of Animals: the general introduction and books 1--3, with Notes. Editions of the two concluding parts of History of Animals, ASL 5.1.b, books 4--6 and ASL 5.1.c, books 7--10, are in preparation. Complete Latin-Arabic and Arabic-Latin indices of History of Animals will be published in due course".